(Invited)HydroGEN: An AWSM Energy Materials Network. (5th April 2018) - Vickers, James W; Dinh, Huyen N.; Randolph, Katie; Weber, Adam Z.; McDaniel, Anthony H.; Boardman, Richard; Ogitsu, Tadashi; Colon-Mercado, Hector; Peterson, David; Miller, Eric L.
Abstract : The HydroGEN (https://www.h2awsm.org/) energy materials network (EMN) aims to accelerate the research and development (R&D) of advanced water splitting (AWS) technologies for clean, sustainable hydrogen production. Announced in October 2016, the HydroGEN EMN comprises six core National Laboratories and focuses on four AWS pathways: low- and high-temperature electrolysis, photoelectrochemical, and solar thermochemical water splitting. The HydroGEN consortium offers an extensive collection of materials research capabilities for addressing R&D challenges in discovery and design, efficacy and efficiency, durability and cost. Leveraging the HydroGEN Consortium's technical experts and broad collection of unique resource capabilities is expected to advance the maturity and technology readiness levels in each advanced water splitting technology pathway.